2013
DOI: 10.1182/blood-2013-04-496281
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screen identifies Jarid1b as a major regulator of mouse HSC activity

Abstract: Key Points• Jarid1b knockdown promotes enhanced HSC activity.Histone methylation is a dynamic and reversible process proposed to directly impact on stem cell fate. The Jumonji (JmjC) domain-containing family of demethylases comprises 27 members that target mono-, di-, and trimethylated lysine residues of histone (or nonhistone) proteins. To evaluate their role in regulation of hematopoietic stem cell (HSC) behavior, we performed an in vivo RNAi-based functional screen and demonstrated that Jarid1b and Jhdm1f p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 41 publications
2
55
1
Order By: Relevance
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…The demethylase LSD1 has July 2015 been shown to maintain endothelium-dependent relaxation. 8 For JARID2, an important role of endocardial-driven cardiac development has been reported. 9,10 The function of the other JARID enzymes in the cardiovascular system has not been studied.…”
mentioning
confidence: 99%
“…14,15 Through this function, JARID1B is involved in the repression of transcription during embryonic development and in embryonic and hematopoietic stem cells. 5,8,11,12,16,17 Therefore, genetic deletion of JARID1B impairs mouse and porcine embryonic development. [18][19][20][21] Considering its effect on gene regulation, we hypothesized that JARID1B affects the expression of endothelial genes and examined the consequences on angiogenesis in human umbilical vein ECs (HUVECs), tamoxifen-inducible conditional, and in the endothelial-specific Jarid1b knockout mouse.…”
mentioning
confidence: 99%
“…A search of the Oncomine database (59,60) showed that JARID1B is up-regulated in multiple types of leukemia (46). JARID1B is important for hematopoietic stem cell renewal (47,48) and is overex- pressed in acute myeloid leukemia. Our data demonstrated a strong increase in expression of JARID1B in B-ALL as compared with normal bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular inhibition of JARID1B using siRNA has shown that JARID1B is important for hematopoietic stem cell renewal (47,48). Here, we tested the effect of pharmacological inhibition of JARID1B on the proliferation of leukemia cells.…”
Section: Inhibition Of Ck2 Restores Ikaros-mediated Repression Of Jarmentioning
confidence: 99%